Towards a new strategy of a chitosan‐based molecularly imprinted membrane for removal of 4‐nitrophenol in real water samples. Issue 7 (30th March 2017) - Di Bello, Maria Pia; Mergola, Lucia; Scorrano, Sonia; Del Sole, Roberta
Abstract: The issue of water contaminants, which affects human and environmental health, is not trivial. It is thus paramount to find new cheap and user friendly ways to detect and remove them from the environment. Here, the synthesis of a green chitosan (CS) based molecularly imprinted membrane for the detection and quantification of 4‐nitrophenol (4‐NO2 Ph) in aqueous media is proposed. The concentration of 4‐NO2 Ph in a water solution was measured by HPLC analysis. CS as a functional polymer, 4‐NO2 Ph as template, 4‐[(4‐hydroxy)phenylazo]benzenesulfonic acid as ligand, and glutaraldehyde as crosslinker in the presence of polyethylene glycol as porogen were used. The membrane was characterized by SEM and Fourier transform IR analyses, which confirmed the CS and polyethylene glycol backbone of the membrane. Kinetic studies of the detection system were performed by using pseudo‐first‐order and pseudo‐second‐order models. Then, the binding efficiency between 195.33 µmol L −1 and 9235.55 µmol L −1 of 4‐NO2 Ph was evaluated, finding a maximum adsorption of 723.25 µmol 4‐NO2 Ph per gram of membrane consistent with the Q max calculated from the Langmuir isotherm. The selectivity of the membrane versus three phenolic competitor molecules, sharing very similar molecular structure to 4‐NO2 Ph, was demonstrated. Finally, the applicability of the membrane to real‐world samples was evaluated, by using drinking water spiked with 7.19 µmol L −1 of 4‐NO2 Ph, obtaining a removal efficiency of 70.6%. © 2017 Society of Chemical Industry Abstract : In the present work, a new biocompatible and low cost chitosan‐based molecularly imprinted membrane for the detection of 4‐NO2 Ph as a model organic contaminant is proposed.